2020
DOI: 10.1038/s41467-020-18028-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide functional analysis of phosphatases in the pathogenic fungus Cryptococcus neoformans

Abstract: Phosphatases, together with kinases and transcription factors, are key components in cellular signalling networks. Here, we present a systematic functional analysis of the phosphatases in Cryptococcus neoformans , a fungal pathogen that causes life-threatening fungal meningoencephalitis. We analyse 230 signature-tagged mutant strains for 114 putative phosphatases under 30 distinct in vitro growth conditions, revealing at least one function for 60 of these proteins. Large-scale virulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 107 publications
0
21
0
Order By: Relevance
“…In Colletotrichum orbiculare , CoWhi2 interacts with CoPsr1 and is involved in the biotrophic infection stage (Harata et al, 2016 ). Systematic analysis of phosphatases in the wheat head blight pathogen Fusarium graminearum and human opportunistic fungal pathogen Cryptococcus neoformans revealed that Psr1 homologs are involved in infection‐related development and virulence (Jin et al, 2020 ; Yun et al, 2015 ). In our study, we found that MoWhi2 colocalized with MoPsr1 on the plasma membrane and functioned together during appressorium development and invasive growth.…”
Section: Discussionmentioning
confidence: 99%
“…In Colletotrichum orbiculare , CoWhi2 interacts with CoPsr1 and is involved in the biotrophic infection stage (Harata et al, 2016 ). Systematic analysis of phosphatases in the wheat head blight pathogen Fusarium graminearum and human opportunistic fungal pathogen Cryptococcus neoformans revealed that Psr1 homologs are involved in infection‐related development and virulence (Jin et al, 2020 ; Yun et al, 2015 ). In our study, we found that MoWhi2 colocalized with MoPsr1 on the plasma membrane and functioned together during appressorium development and invasive growth.…”
Section: Discussionmentioning
confidence: 99%
“…In the field, significant progress has been made in the characterization of enolase, an enzyme implicated in tissue invasion, as well as enzymes from the mannitol biosynthesis and de novo purine biosynthesis pathways in many pathogenic fungi. In addition to the pathways explored in this review, de novo pyrimidine biosynthesis enzymes, intracellular redox environment regulators and key phosphatases, kinases and transcription factors that form cellular signaling networks have been explored as potential antifungal drug targets (Oliver et al, 2016 ; Marshall et al, 2019 ; Jin et al, 2020 ). Altogether, these experiments lay the foundation for antifungal drug discovery projects that target unconventional, but promising, pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic fungi show lower conservation and greater diversity in phosphoproteins compared to higher eukaryotes, with the functionally important phosphoproteins being the more highly conserved [ 6 , 7 , 8 , 9 ]. Kinase and phosphatase orthologs are heterogeneously distributed across fungal species and often show diversified functions depending on habitats and activities [ 10 , 11 , 12 , 13 ]. Orthologs of protein tyrosine kinases of higher eukaryotes are lacking in unicellular fungi [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Mpk1 ‘cell wall integrity’ pathway, the ‘high osmolality glycerol’ (Hog1) stress response pathway and the Fus3/Kss1 mating and filamentation pathways, independently and cooperatively, play essential roles in fungal growth, development, virulence and adaptation to stress [ 15 , 16 , 18 ]. Fungal MAP kinases are generally highly conserved but show considerable functional divergence in number of MAPK genes and in activation loop motifs [ 6 , 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%